Relationships between dental hygienists' work environment and patient safety culture - Eun-Mi Choi; So-Jung Mun; Won-Gyun Chung; Hie-Jin Noh (BMC, 2019)
Abstract Background Patient safety culture is a core factor in increasing patient safety, is related to the quality of medical service, and can lower the risk of patient safety accidents. However, in dentistry, research has previously focused mostly on reporting of patient safety accidents. Dental professionals' patient safety culture must therefore first be assessed, and related factors analyzed to improve patient safety. Methods This cross-sectional study completed a survey on 377 dental hygienists working in dental settings. To assess patient safety culture, we used a survey with proven validity and reliability by translating the Hospital Survey on Patient Safety Culture (HSOPS) developed by Agency for Healthcare Research and Quality (AHRQ) into Korean. Response options on all of the items were on 5-point Likert-type scales. SPSS v21 was used for statistical analysis. The relationships between workplace factors and patient safety culture were examined using t-tests and one-way analysis of variance (ANOVA) tests(p < 0.05). Results The work environment of dental hygienists has a close relationship with patient safety. Dental hygienists working ≥40 h/week in Korea had a significantly lower for patient safety grade than those working < 40 h/week. When the number of patients per day was less than 8, the safety level of patients was significantly higher. And significant differences were found depending on institution type, institution size. Conclusions In order to establish high-quality care and patient safety system practical policies must be enacted. In particular, assurance in the quality of work environment such as sufficient staffing, appropriate work hours, and enough rest must first be realized before patient safety culture can easily be formed.